2020
DOI: 10.7454/jki.v23i1.1073
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Minority Stress on Level of Depression among Thai LGBT Adults

Abstract: In the US, lesbian, gay, bisexual, and transgender (LGBT) individuals report higher rates of depression compared with heterosexual and cisgender persons. To date, little is known about the mental health of LGBT adults in Thailand. Here, we examined rates and correlates of depression among a volunteer sample of Thai LGBTs. Data were collected as part of a larger cross-sectional survey study. Standardized measures of sexual orientation and gender identity, stress, coping style, and minority stressors were comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 21 publications
1
4
0
Order By: Relevance
“…Among the specific mental disorders, the one with the highest prevalence is major depressive disorder, which is at least 3 times (40.1% vs. 12%) [ 33 ] and as high as 20 times (40.1% vs. 2.3%) [ 2 ] more prevalent than in the Malaysian general population. This is comparable to a Thai study with similar populations, where the prevalence of depression was found to be 40.3% [ 34 ], and a multinational Southeast Asian study, which found depression to be in 23.5% of its sample [ 35 ]. Although there is no recent source for the prevalence of suicidal behavior disorder or suicide attempts for the general Malaysian population, our study found that 21.1% of our participants fulfilled the criteria of suicidal behavior disorder, compared with the Thai data of 13.1% [ 36 ] and the multinational Southeast Asian data of 35.3% [ 35 ].…”
Section: Discussionsupporting
confidence: 84%
“…Among the specific mental disorders, the one with the highest prevalence is major depressive disorder, which is at least 3 times (40.1% vs. 12%) [ 33 ] and as high as 20 times (40.1% vs. 2.3%) [ 2 ] more prevalent than in the Malaysian general population. This is comparable to a Thai study with similar populations, where the prevalence of depression was found to be 40.3% [ 34 ], and a multinational Southeast Asian study, which found depression to be in 23.5% of its sample [ 35 ]. Although there is no recent source for the prevalence of suicidal behavior disorder or suicide attempts for the general Malaysian population, our study found that 21.1% of our participants fulfilled the criteria of suicidal behavior disorder, compared with the Thai data of 13.1% [ 36 ] and the multinational Southeast Asian data of 35.3% [ 35 ].…”
Section: Discussionsupporting
confidence: 84%
“…Without a supportive environment comprised of individuals who gay and bisexual men trust and who they share positive character traits with, men may have trouble processing emotional and physical discrimination that can fester feelings of depression and internalization homonegativity, factors which have been associated with IPV [16,24]. When considering reports that almost all MSM had experienced some form of homophobia in one study, and another study which reported that half of MSM discrimination events are connected to sexual orientation or gender identity, this becomes especially relevant [25,26]. There has been an increase in recent years towards research catered to Thai gay and bisexual male communities, however there still remains a gap in understanding the effect that sexual orientation disclosure has on depression and the potentially influential role of other variables, including social support and IPV.…”
Section: Sexual Orientation Disclosurementioning
confidence: 99%
“…We did not find associations between other minority stressors and depressive symptoms. However, a study in Thailand suggested that experiences of victimization, discrimination, and identify concealment also predicted depression among sexual minorities [83]. More research is needed to confirm the relationship between various minority stressors and depressive symptoms in different cultural contexts.…”
Section: Discussionmentioning
confidence: 99%